Демократичні і авторитарні режими в умовах соціальних і економічних криз - Зєнкін Михайло Васильович; Кулик Віталій Олександрович; Саламаха Ігор Павлович (My University, 2025)
Дослідження в статті присвячене особливостям функціонування демократичних та авторитарних політичних режимів в умовах соціальних та економічних криз. Соціально-економічні проблеми, зокрема фінансові кризи, пандемія, війна, різні політичні процеси по-різному впливають на ефективність управління та стійкість політичних систем будь-якої країни світу. The study in the article is devoted to the peculiarities of the functioning of democratic and authoritarian political regimes in conditions of social and economic crises. Socio-economic problems, in particular financial crises, pandemics, wars, various political processes, have different effects on the efficiency of governance and the stability of political systems of any country in the world. Democratic regimes, which are based on the principles of citizen participation, openness and political pluralism, as a rule, have flexible mechanisms for responding to external threats, but they can often face difficulties that make it impossible to make timely and effective decisions due to excessive bureaucracy, the need to coordinate certain issues between different branches of government and the existence of various political interests that cause a delay in the development of the state in conditions of crisis.
Democratic and authoritarian regime in the conditions of social and economic crisis
Keywords: політичні режими; демократія; авторитаризм; соціальна криза; політична стабільність; політична система; політична адаптація; перехідні режими.; political regimes; democracy; authoritarianism; social crisis; political stability; political system; political adaptation; transitional regimes